2014
DOI: 10.3892/mmr.2014.3036
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 inhibits lung cancer cell metastasis

Abstract: Previous studies have identified a variety of microRNAs (miRNAs) that have important roles in cancer progression, particularly in tumor invasion and metastasis. Downregulation of miR‑145 was reported to occur in various types of human cancer; however, the role of miR‑145 in lung cancer metastasis and its potential mechanisms of action remain to be elucidated. The present study aimed to investigate the effects of miR‑145 on metastasis and epithelial‑mesenchymal transition (EMT) in A549 human lung adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Our observation was closely consistent with a recently published report demonstrating that UCA1 promoted bladder cancer cell migration and invasion by the hsa-mir145-ZEB1/2-FSCN1 pathway (24). Similar to miR-143, miR-145 was also reported to be a tumor suppressive gene and a negative regulator of EMT (47)(48)(49). Thus, UCA1 might function as an oncogene by sponging EMT-related miRNAs.…”
Section: Discussionsupporting
confidence: 81%
“…Our observation was closely consistent with a recently published report demonstrating that UCA1 promoted bladder cancer cell migration and invasion by the hsa-mir145-ZEB1/2-FSCN1 pathway (24). Similar to miR-143, miR-145 was also reported to be a tumor suppressive gene and a negative regulator of EMT (47)(48)(49). Thus, UCA1 might function as an oncogene by sponging EMT-related miRNAs.…”
Section: Discussionsupporting
confidence: 81%
“…These results demonstrate that miR-664 may serve an important role in lung cancer. The risk of distant metastasis of lung cancer is high and once metastasis occurs, it may become an incurable disease with limited survival time (29). The EMT serves an important role in metastasis and allows epithelial cells to lose their epithelial characteristics and acquire a mesenchymal phenotype (30).…”
Section: Discussionmentioning
confidence: 99%
“…Through further qRT-PCR validation, overexpressed miR-1260b was demonstrated in LN metastasis tissue of NSCLC patients compared with LN free NSCLC patients. A variety of studies have identified certain miRNAs that suppress the metastasis in lung cancer [9,10,21]. Let-7 is one of the earliest identified miRNAs with significantly reduced expression in a large number of malignant tumors and is known to attenuate the development of lung cancer [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Human microRNA genes are frequently located at cancer-associated genomic regions or in fragile sites [8]. In recent studies, several miRNAs such as miR-145, miR-186 and the let-7 family were considered suppressors for the metastasis and epithelial mesenchymal transition (EMT) in lung cancer [2,9,10] while miR-10b and miR-155 were positively correlated with the NSCLC tumorous process [11,12]. Therefore, there is a need to investigate the specific miRNAs as putative indicators for NSCLC metastasis more comprehensively and provide a sensitive method for the early diagnosis of NSCLC.…”
mentioning
confidence: 99%